IMPLEMENTASI ECO-EDUCATION DI SEKOLAH PERKOTAAN MELALUI BUDIDAYA VERTIKULTUR TANAMAN HORTIKULTURA ORGANIK - Budiwati, Siti Mariyam, Tutiek Rahayu (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2014)
The purpose of this activity were: (1) Providing instructional media with eco-education minded at the urban school with limited land area; (2) Providing knowledge about the benefits of a healthy environment and organic foods; (3) Providing verticultural farming of organic horticultural plant skills to students. This service activities conducted with visiting the location, namely in SMP Muhammadiyah 5 Patehan Lor Road Yogyakarta. The target activity were 5 teachers and 25 students, the activities initiated by the pretest and ending with posttest. The activities included: (1) presenting the material of a healthy environment and healthy food, nutritious and environmentally friendly; (2) demonstrating and practicing of verticultural farming of organic horticultural plants; (3) evaluating the effectiveness of action after one month activities. The evaluation was carried out by reviewing the one month activities to see success of practiced verticultural cultivation. Then, given a questionnaire sheet about the activities benefits, and knowing the activities advantages and disadvantages. This service activities could be said to be successful because all participants were practicing the verticultural farming of organic horticultural plants in a groups. Keywords: eco-education, verticultural cultivation, and organic horticultural plants